IMPLEMENTATION OF EARLY WARNING SYSTEM SCORE (EWSS) IN HOSPITALIZED PATIENT: A LITERATURE REVIEW - Rodina Sinaga; Evelyn Hemme Tambunan (Nursing Sciences Journal, 2025)
The Early Warning System Score (EWSS) is increasingly recognized as an essential tool for identifying clinical deterioration in hospitalized patients. This literature review synthesizes the outcomes and practical aspects of EWSS implementation over the past decade, with a focus on studies conducted in teaching, community, and specialized care hospitals. Articles indexed in English databases PubMed, MEDLINE, Embase, and the Cochrane Library. The research steps were performed according to PRISMA writing standard and the quality assessment was done using CASP critical appraisal tools due to the heterogeneity of the study designs according to the inclusion criteria. Drawing from over 26 scholarly sources—80% of which have been published within the last five years the review examines key implementation metrics such as patient safety  indicators, staff response times, and cost-effectiveness while detailing the assessment tools and measurements used to evaluate EWSS outcomes. Quantitative data were analyzed to assess success rates and pinpoint failure points across multiple hospital departments including emergency, intensive care, and in-patient wards. Implementation challenges related to staff training, resource allocation, and integration with existing patient monitoring systems are discussed, along with recommendations to enhance system performance and clinical decision-making. The findings suggest that while EWSS can significantly improve early detection of clinical deterioration, its success is contingent upon tailored implementation strategies that consider the unique constraints of varied hospital types. This review contributes to a better understanding of how global standards and local practices interact in the effective utilization of EWSS, ultimately aiming to improve patient outcomes and hospital safety.